Excited‐State Topology Modifications of the Dihydroazulene Photoswitch Through Aromaticity. Issue 8 (5th June 2019) - Skov, Anders B.; Ree, Nicolai; Gertsen, Anders S.; Chabera, Pavel; Uhlig, Jens; Lissau, Jonas S.; Nucci, Luigi; Pullerits, Tõnu; Mikkelsen, Kurt V.; Brøndsted Nielsen, Mogens; Sølling, Theis I.; Hansen, Thorsten
Abstract: The gain and loss of aromaticity plays a key role in organic chemistry and in the prediction of rate‐determining steps. Herein, we explore the concept of aromaticity in photoisomerization reactions. Benzannulated derivatives of the dihydroazulene‐vinylheptafulvene (DHA‐VHF) photoswitch were investigated using transient absorption spectroscopy and time‐dependent density functional theory to elucidate the effect of built‐in aromaticity on the switching properties. We found that benzannulation hampered the switching ability by enhancing an already existing barrier on the excited state surface. This enhancement was found to arise from a significant loss of aromaticity in the DHA‐to‐VHF transition state on the excited state potential energy surface. The VHF was found to be highly aromatic on the excited state surface, showing a reversal of aromaticity compared to the ground state. The barrier was found to be dependent on the position of benzannulation, since one derivative was found to switch as fast as the non‐benzannulated molecule although with lower efficiency, whereas another derivative completely lost the ability to undergo reversible photoswitching. The findings herein provide novel principles for the design of molecular photoswitches, shedding new light on excited state aromaticity, as previous discussions have mainly considered excited state aromaticity to be beneficial to switching. Our findings show that this view must be reconsidered. Abstract : Didn′t see that coming ! Excited state aromaticity has been proposed as a way of improving the efficiency of photoswitches by removing excited state barriers. We show that by introducing excited state aromaticity into the dihydroazulene‐vinylheptafulvene (DHA‐VHF) photoswitch, we reduce the switching efficiency by enhancing an excited state barrier, contrary to what is expected.